Kagurabachi. 04 - Hokazono, Takeru (Shonen Jump manga., 2025)
"Chihiro's cursed past sends him down a quest of bloody vengeance! The Shinuchi--the strongest sword ever produced by Kunishige--is up for auction. Chihiro's on a quest to reclaim the famed blade, but first he'll have to deal with the auction's guards, who are sworn to protect the auction at all costs. Undaunted in his quest for vengeance, Chihiro vows to cut them all down!"--Publisher.